In situ synthesis of Al2O3‐supported ZnCr2O4 nanoparticles for application as an activated photocatalyst. Issue 2 (21st December 2016) - Tajizadegan, Hamid; Naghibi, Sanaz; Jamshidi, Amin; Torabi, Omid; Golabgir, Mohammad‐Hossein
Abstract: Zincochromite nanoparticles (NPs) were precipitated on surfaces of the as‐prepared Al2 O3 micron‐sized particles by a heterogeneous precipitation technique using urea as a homogeneous precipitation agent. This procedure leads to decrease the pore diameter and increase the pore volume and specific surface area ( a s ), realizing the potential access to ZnCr2 O4 catalytic sites. Although the obtained band gap energy (Eg ) of Al2 O3 ‐ZnCr2 O4 composite is about 2.3 eV (more than ZnCr2 O4 ), the absorbance is enhanced about 1.5 orders of magnitude. These characteristics make it an effective photocatalyst of inorganic dyes from an aqueous media. Dye removal performance of the nanocomposite powder is higher than that of pure ZnCr2 O4, which is attributed to an increase in the photocatalytic sites and the absorbance intensity. It was believed that the surface area created from Al2 O3 support realized the potential access to ZnCr2 O4 catalytic sites. To confirm these assertions, X‐ray diffractometry (XRD), scanning electron microscopy (SEM), diffuse reflectance spectroscopy (DRS), and N2 adsorption‐desorption analysis were applied.